"Decarbonization" of an imino-N-heterocyclic carbene ligand via triple benzyl migration from hafnium12. Issue 31 (19th March 2015) - Prema, Dipesh; Mathota Arachchige, Yohan L. N.; Murray, Rex E.; Slaughter, LeGrande M.
Abstract : Binding of an imino-N-heterocyclic carbene to tetrabenzylhafnium triggers complete removal of the carbene carbon via three successive benzyl migrations. Abstract : An imino-N-heterocyclic carbene underwent three sequential benzyl migrations upon reaction with tetrabenzylhafnium, resulting in complete removal of the carbene carbon from the ligand. The resulting eneamido–amidinato hafnium complex showed alkene polymerization activity comparable to that of a precatalyst containing the intact iminocarbene ligand.